Systemic Venous Inflow to the Liver Allograft to Overcome Diffuse Splanchnic Venous Thrombosis - Cristian Lupascu; Tom Darius; Pierre Goffette; Jan Lerut (Gastroenterology Research and Practice)
Diffuse splanchnic venous thrombosis (DSVT), formerly defined as contraindication for liver transplantation (LT), is a serious challenge to the liver transplant surgeon. Portal vein arterialisation, cavoportal hemitransposition and renoportal anastomosis, and finally combined liver and small bowel transplantation are all possible alternatives to deal with this condition. Five patients with preoperatively confirmed extensive splanchnic venous thrombosis were transplanted using cavoportal hemitransposition (4x) and renoportal anastomosis (1x). Median follow-up was 58 months (range: 0,5 to 130 months). Two patients with previous radiation-induced peritoneal injury died, respectively, 18 days and 2 months after transplantation. The three other patients had excellent long-term survival, despite the fact that two of them needed a surgical reintervention for severe gastrointestinal bleeding. Extensive splanchnic venous thrombosis is no longer an absolute contraindication to liver transplantation. Although cavoportal hemitransposition and renoportal anastomosis undoubtedly are life-saving procedures allowing for ensuring adequate allograft portal flow, careful follow-up of these patients remains necessary as both methods are unable to completely eliminate the complications of (segmental) portal hypertension.